Answer:
Step-by-step explanation:
prime factors of 20 = 2 * 2 * 5
![\frac{7}{20}=\frac{7}{2*2*5}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B20%7D%3D%5Cfrac%7B7%7D%7B2%2A2%2A5%7D)
A. seven tents b. seven hundredths c. seven tents
<h3>The lateral area for the pyramid with the equilateral base is 144 square units</h3>
<em><u>Solution:</u></em>
The given pyramid has 3 lateral triangular side
The figure is attached below
Base of triangle = 12 unit
<em><u>Find the perpendicular</u></em>
By Pythagoras theorem
![hypotenuse^2 = opposite^2 + adjacent^2](https://tex.z-dn.net/?f=hypotenuse%5E2%20%3D%20opposite%5E2%20%2B%20adjacent%5E2)
Therefore,
![opposite^2 = 10^2 - 6^2\\\\opposite^2 = 100 - 36\\\\opposite^2 = 64\\\\opposite = 8](https://tex.z-dn.net/?f=opposite%5E2%20%3D%2010%5E2%20-%206%5E2%5C%5C%5C%5Copposite%5E2%20%3D%20100%20-%2036%5C%5C%5C%5Copposite%5E2%20%3D%2064%5C%5C%5C%5Copposite%20%3D%208)
<em><u>Find the lateral surface area of 1 triangle</u></em>
![\text{ Area of 1 lateral triangle } = \frac{1}{2} \times opposite \times base](https://tex.z-dn.net/?f=%5Ctext%7B%20Area%20of%201%20lateral%20triangle%20%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20opposite%20%5Ctimes%20base)
![\text{ Area of 1 lateral triangle } = \frac{1}{2} \times 8 \times 12\\\\\text{ Area of 1 lateral triangle } = 48](https://tex.z-dn.net/?f=%5Ctext%7B%20Area%20of%201%20lateral%20triangle%20%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%208%20%5Ctimes%2012%5C%5C%5C%5C%5Ctext%7B%20Area%20of%201%20lateral%20triangle%20%7D%20%3D%2048)
<em><u>Thus, lateral surface area of 3 triangle is:</u></em>
3 x 48 = 144
Thus lateral area for the pyramid with the equilateral base is 144 square units
n, n + 2, n + 4, n + 6 - four consecutive odd integers
-72 - the sum
The equation:
n + (n + 2) + (n + 4) + (n + 6) = -72
n + n + 2 + n + 4 + n + 6 = -72
4n + 12 = -72 |subtract 12 from both sides
4n = -84 |divide both sides by 4
n = -21
n + 2 = -21 + 2 = -19
n + 4 = -21 + 4 = -17
n + 6 = -21 + 6 = -15
Answer: -21, -19, -17, -15.
Use the slope formula y2-y1/x2-x1
3-(-7)/1-(-1) = 10/2 = 5
To find the y-intercept:
y=5x+b
3=5(1)+b
3 = 5+b
-5 -5
-2=b
The equation of the line that passes through (-1,-7) and (1,3) is
y=5x-2